Leptin Beyond the Lipostat: Key Component of Blood Pressure Regulation - Kusminski, Christine M. (Circ Res, 2015)
Obese individuals often struggle with increases in blood pressure that ultimately lead to an enhanced cardiovascular disease risk. The mechanistic basis for this association has remained largely unknown. While a large number of metabolic signals are altered in obese individuals, including dyslipidemia, associated changes in sphingolipids and an overall increase in subclinical inflammation, none of these parameters are thought to greatly influence blood pressure. Recent data suggests that the adipokine leptin, whose circulating levels are typically proportional to fat mass, is a major driving force for the obesity-associated increases in blood pressure. The effects of leptin on blood pressure are mediated by neuronal circuits, including leptin-responsive neurons in the dorsomedial hypothalamic nucleus.